A new fossil wood of Peltophoroxylon (Leguminosae: Caesalpinioideae) from the El Palmar Formation (late Pleistocene), Entre Ríos, Argentina - Brea, Mariana (2014)
This paper describes the first record of Peltophoroxylon (Ramanujam) Müller-Stoll et Mädel 1967 from the late Pleistocene of Argentina. The fossil specimens were recovered from the Colonia Ayuí and Punta Viracho fossil localities of the El Palmar Formation, located in the middle part of the Uruguay Basin, eastern Argentina. The diagnostic features are: growth ring boundaries demarcated by marginal parenchyma, medium-sized vestured intervessel pits, vessel-ray parenchyma pits similar in size and shape to intervessel pits, vasicentric to lozenge type aliform axial parenchyma, biseriate (70%) and uniseriate (30%) homocellular rays, non-septate and septate fibers, and long chains (10+) of prismatic crystals in chambered axial parenchyma cells. These features suggest a relationship with Peltophorum (Vogel) Benth. (Leguminosae: Caesalpinioideae). The vessel diameter and vessel density of the El Palmar woods are consistent with the temperate-warm, humid-semiarid climate inferred for this region during the late Pleistocene.